The relationship of selected demographic variables with the desired degree of participative management of professional librarians in the University of the Philippines Diliman Libraries - Dela Cruz, Rogelyn Trina C. (2002)
Participative management (PM) is a management style which lays stress on the importance of worker's participation in the decision making process. This study consisted of 58 professional librarians occupying College Librarian I, II, and III positions in the University of the Philippines Diliman (UPD) Libraries. It made use of the questionnaire survey method to find out the demographic profile of professional librarians employed in the UPD libraries and its relationship with the desired degree of participative management of professional librarians including the organizational structure and activities in libraries through which librarians participate in the decision making process. Results of the study show that majority of the professional librarians employed in the University of the Philippines Diliman libraries are female and are married; they belong to the age bracket 51-55 years; they are MLS graduates, and they have been in service for "21 years and above." The chi square test in the Statistical Package for social Sciences was used to determine if there is a significant relationship between the demographic variables and the desired degree of PM of professional librarians in the UPD libraries. The variables which had a positive relationship are gender, librarian's length of service, and librarian's awareness of the mission/vision/goal of the library. Those that showed a negative relationship are age, civil status, and the educational background.